2022
DOI: 10.1101/2022.01.06.22268711
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulatory T-cells are central hubs for age-, sex- and severity-associated cellular networks during COVID-19

Abstract: Using single-cell proteomics by mass cytometry, we investigate changes to a broad selection of over 10,000,000 immune cells in a cohort of moderate, severe, and critical Japanese COVID-19 patients and healthy controls with a particular focus on regulatory T-cells (Tregs). We find significant disruption within all compartments of the immune system and the emergence of atypical CTLA-4high CD4 T-cells and proliferating HLA-DRlowCD38high Tregs associated with critical patients. We also observed disrupted regulatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Moreover, our results align with those observed by Søndergaard et al . [ 40 ], where Treg expressing CD38 marker were increased related to COVID-19 severity. The Treg-expressing CD38 subset has been described as a Treg subset with a high immunosuppressive ability [ 41 , 42 ], and the expression of CD38, in this case, could explain the activation of the Treg and complete the list of functional markers described by Vick et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results align with those observed by Søndergaard et al . [ 40 ], where Treg expressing CD38 marker were increased related to COVID-19 severity. The Treg-expressing CD38 subset has been described as a Treg subset with a high immunosuppressive ability [ 41 , 42 ], and the expression of CD38, in this case, could explain the activation of the Treg and complete the list of functional markers described by Vick et al .…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immune responses are also modulated by SARS-CoV-2 infection. Several studies report decreases in CD4 + T cells, CD8 + T cells, CD4 + FoxP3 + regulatory T cells (Tregs), MAIT (CD8 + mucosal-associated invariant T) cells, γδ T cells, and αβ T cells in persons with mild or severe COVID-19 (25)(26)(27)(28). Conversely, increases in the ratio of CD4 + /CD8 + T cells, or Tregs number, have also been reported in persons with COVID-19 (29,30).…”
Section: The Impact Of Acute Sars-cov-2 Infection On the Immune Systemmentioning
confidence: 99%
“…Notably, the counts of total T cells, including CD4 + and CD8 + T cells, are reduced in persons with COVID-19 and adversely associated with survival (71). Moreover, the proportion or counts of Tregs, MAIT cells, γδ T cells, and αβ T cells are correspondingly reduced in persons with mild or severe COVID-19 (25)(26)(27)(28). Strikingly, it has been reported that T cells are functionally exhausted (defined by upregulated expression of Fas, PD-1, CTLA-4, TIGIT, and TIM-3, and downregulated expression of granzyme B, IFN-γ, IL-2, and TNF) in persons with COVID-19 (31).…”
Section: T Cellsmentioning
confidence: 99%